Influence of Use Backing Ceramic to Value Yield Strength on ASTM A36 Steel Using SMAW Welding - Hamzah Hamzah (Collaborate, 2023)
Welding large structures often requires alternating welding on both sides, which is time-consuming and costly. To overcome this, the media backing ceramics are used as hot melt barriers to form better results, speed up the ship welding process and reduce budgets. This study aims to determine the effect of media use baking ceramics against tensile strength test on ASTM A36 steel by SMAW welding. The calculation results show a strong effect on ASTM A36 steel. MarkYield strength is the highest found in specimens that do not use baking ceramics, equal to 322.413Mpa, while the valueYield strength is the lowest found in testing that uses baking ceramics at 309.92 Mpa.